The Evolution of the Polymerase Chain Reaction to Diagnose Childhood Infections - Rogers, Beverly Barton (Pediatric and developmental pathology, 2015)
Children's healthcare has evolved over the years, and the pediatric laboratory has contributed to the clinical understanding of childhood disease through the application of new technology and knowledge. This article highlights the evolution of PCR technology to aid in the diagnosis of pediatric infections, from the discovery of the PCR, through the subsequent years when the clinical need exceeded the capability of the technology, until the current day, when application of the PCR is becoming commonplace.